2020
DOI: 10.1177/0734242x19894632
|View full text |Cite
|
Sign up to set email alerts
|

Status of waste-to-energy in Germany, Part I – Waste treatment facilities

Abstract: This study gives a detailed overview over the German waste-to-energy sector in 2015. The aim is to quantify the available treatment capacities and the energetic potential of waste in Germany. The work is based on an extensive data collection and evaluation, both from literature sources as well as from a survey among operators of waste treatment plants. The present Part I, gives an overview of all treatment facilities in Germany that convert waste into energy. It was found that in total, almost 320 PJ of end en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The centrality shown by Germany can also be seen in the literature, as there has been a thorough analysis of waste treatment facilities in this country [69].…”
Section: Discussionmentioning
confidence: 88%
“…The centrality shown by Germany can also be seen in the literature, as there has been a thorough analysis of waste treatment facilities in this country [69].…”
Section: Discussionmentioning
confidence: 88%
“…In contrast to waste incineration and co-incineration, which produce energy and even contribute to 3.7% of the German end energy consumption [72], gasification requires external energy. The use of energy from renewable sources for this purpose is environmentally favorable, but requires energy storage.…”
Section: Solar Energy Storagementioning
confidence: 99%
“…The latest reports have shown that there are 66 municipal waste incinerators currently in operation in Germany, covering 3.7 % of the country's energy needs. By 2016, licensed installations were able to burn 20.2 million tons of waste, that can't be recycled otherwise, using the most advanced technologies [3].…”
Section: Ordinance On Environmentally Compatible Storage Of Waste From Human Settlements and On Biological Waste-treatment Facilities Of mentioning
confidence: 99%
“…Analysis of recent research and publications. Several researchers in the EU devoted their work to the deep analysis of the WM legal system, the most relevant ones to be mentioned are N. Faris and S. Lieberz [1], H. Schnurer [2], K. Weber, P. Quicker, J. Hanewinkel and Flamme S. [3], V.А. Zujev [4].…”
mentioning
confidence: 99%